Enhanced alcohol-seeking behavior by nicotine in the posterior ventral tegmental area of female alcohol-preferring (P) rats: modulation by serotonin-3 and nicotinic cholinergic receptors - Hauser, Sheketha R. (Psychopharmacology (Berl), 2014)
RATIONALE: Alcohol and nicotine co-use can reciprocally promote self-administration and drug-craving/drug-seeking behaviors. To date, the neurocircuitry in which nicotine influences ethanol (EtOH) seeking has not been elucidated. Clinical and preclinical research has suggested that the activation of the mesolimbic dopamine system is involved in the promotion of drug seeking. Alcohol, nicotine, and serotonin-3 (5-HT(3)) receptors interact within the posterior ventral tegmental area (pVTA) to regulate drug reward. Recently, our laboratory has reported that systemic administration of nicotine can promote context-induced EtOH seeking. OBJECTIVES: The goals of the current study were to (1) determine if microinjections of pharmacologically relevant levels of nicotine into the pVTA would enhance EtOH seeking, (2) determine if coadministration of nicotinic cholinergic receptor antagonist (nACh) or 5-HT(3) receptor antagonists would block the ability of nicotine microinjected into the pVTA to promote EtOH seeking, and (3) determine if 5-HT(3) receptors in the pVTA can modulate EtOH seeking. RESULTS: Nicotine (100 and 200 µM) microinjected into the pVTA enhanced EtOH seeking. Coinfusion with 200 µM mecamylamine (nACh antagonist) or 100 and 200 µM zacopride (5-HT(3) receptor antagonist) blocked the observed nicotine enhancement of EtOH seeking. The data also indicated that microinjection of 1 µM CPBG (5-HT(3) receptor agonist) promotes context-induced EtOH seeking; conversely microinjection of 100 and 200 µM zacopride alone reduced context-induced EtOH seeking. CONCLUSIONS: Overall, the results show that nicotine-enhanced EtOH-seeking behavior is modulated by 5-HT(3) and nACh receptors within the pVTA and that the 5-HT(3) receptor system within pVTA may be a potential pharmacological target to inhibit EtOH-seeking behaviors.